Development of Android-based Augmented Reality Learning Media Through Project Based Learning on Flat Side Building Materials to Improve Students' Mathematical Spatial Abilities at SMPN3 Medan - Alawiyah, Tuti (JMEA : Journal of Mathematics Education and Application, 2024)
Augmented Reality is a technology that is able to combine the real and virtual worlds by displaying three-dimensional (3D) objects on the device's camera media so that on the device screen you can see 3D objects that appear to exist in the real world. This research aims to develop and test the feasibility of an Augmented Reality-based module that can improve students' spatial abilities. This research is development research with the Plomp development model which consists of: Preliminary Investigation; Design; Realization; Test, Evaluation, and Revision. The instruments used were expert validation sheets, observation sheets, interview guidelines, teacher and student response questionnaires, learning outcomes tests, pretest and posttest of student spatial abilities. The types of data are qualitative data and quantitative data. The data analysis carried out was expert team validation data analysis, practicality data analysis, and effectiveness data analysis. The research results show that the material expert score is 91.53% and the design expert score is 90.53%, which is in the very valid category. The module has also been declared practical as seen from the teacher response questionnaire score of 80.00% in the practical category, and the questionnaire score in the small group trial of 84.26% and in the field test of 84.38% in the very practical category. Effectiveness is shown by 83.33% of students completing the learning outcomes test, and the results of the N-Gain calculation show that 11 students experienced a moderate increase in spatial ability and 13 students experienced a high increase in spatial ability. Based on the research results, it can be concluded that the Augmented Reality-based module for flat-sided building material that has been developed is suitable for use as learning teaching material. The research objective is to develop learning media with Android-based augmented reality in junior high school level mathematics lessons. The research method used to develop this learning media is a type of research and development (RND). The development model used is the ADDIE model with stages Analysis, Design, Development, Implementation, and Evaluation. In this research, the product has been validated by media experts, material experts and language experts, as well as students on a small scale. The results of the validation of experts and students can be concluded that learning media with Android-based augmented reality is in the very feasible category with the validation percentage obtained by media experts 95%, material experts 93.28%, language experts 87.5% and student validation 90.19%. So that learning media with Android-based augmented reality is suitable for use as a mathematics learning media for junior high school level.